FTIR, a powerful technique in organic coatings failure diagnosis - Costa, Maria do Rosário (2010)
FTIR spectrometry (Fourier Transform Infrared) is an instrumental technique of analysis that presents significant advantages on the dispersive traditional system, such as the increase of the relation signalnoise, the capacity of getting absorption spectra of low energy and therefore, bands of absorption of weak intensity. This technique is widely used in study, resin characterization and evaluation of polymeric materials as well as of its degradation when exposed to the most varied conditions of service, or still in the analysis and diagnosis of defects that occur during the application or production process. Techniques connected to the FTIR had more recently appeared as the photoacoustic (PAS-FTIR), the microscopy (MCT-FTIR) and the attenuated total reflectance (ATR), which allow to analyze weekly transparent and dark samples without removal of coatings from the substrates. The choice of the technique to use depends on the morphology of the surfaces to analyze and the type of failure in cause (lack of adhesion, contamination, aging degradation, etc). In this work the application of FTIR and techniques associates to the identification of the causes that had originated diverse types of defect in applied organic coatings on polymeric materials is presented. Key words: FTIR, Organic Coatings, Failure Diagnosis